Pendampingan Pengelolaan Keuangan Desa Menurut PDTT 07 Tahun 2021 - Irawan Irawan; Erlina Erlina; Iskandar Muda; Esa Setiana; Debbi Chyntia Ovami; Junawan Junawan (Journal of Social Responsibility Projects by Higher Education Forum, 2023)
The purpose of implementing this service is to provide a deeper understanding regarding village financial management. The current implementation of village fund management refers to the Regulation of the Minister of Villages, Development of Disadvantaged Regions, and Transmigration (PDTT) of the Republic of Indonesia Number 7 of 2021 concerning Priority for Using Village Funds with village authority. PPM activities have been carried out smoothly and have provided Village Apparatus knowledge and skills regarding village financial management according to Permendes PDTT no 7 of 2021 Village apparatus should consistently implement the role of Village Accounting within the Village government environment in accordance with existing regulations. The results of this service can also be concluded that village financial management is a form of village accountability to the community and the central government. Community service activities regarding village financial management have been carried out in accordance with the plan, namely providing provision for understanding and ability to carry out planning, administration and reporting as well as accountability. This activity needs to be followed up with administrative management which is still lacking. Village apparatus should be able to formulate problems, gather relevant ideas, synthesize and evaluate information and apply ideas to make Village government financial performance analysis.